The Impact of Training Methods and Leg Muscle Strength to the Long Jumping Squat Style Skills of SMA Pesantren Pancasila Bengkulu - Defliyanto; Moch. Asmawi; Hernawan Hernawan (UNIB Press, 2023)
The purpose of this study was to determine the impact of the Training methods (Plyometrik and Weight Training ) and in terms the high strength of leg muscle and the low strength of leg muscle. Based on the problems, the design of this study was the treatment by the level of 2 x 2. Analysis of variance between the group at a significant level α = 0.05. This study also aims to determine the interaction between exercise and leg muscle strength against to the long jumping squat style skills.This study was done in SMA Pesantren Pancasila, Bengkulu. The sample was consisted of 24 athletes in this study, then divided into four groups, each group consisting of 6 athletes which as the object of this study.The data analysis technique was the analysis of variance of two lanes and then followed by Tukey test with significance level α = 0.05. The results of this study indicate that (1) Overall, the results of long jumping skills to the group that trained with exercise methods of Plyometrik better than the group trained with the type of Weight Training, (2) There are interactions between the Training methods with leg muscle strength to the results of Long Jumping Squat Style Skills, (3) For those athletes who have high leg muscle strength, the result of long jumping skills through the implementation of exercise methods Plyometrik better than the method of Weight Training, (4) For those athletes who have low leg muscle strength, the result of long jumping skill through the implementation of Weight Training methods not better than the Training methods of Plyometrik.